2010
DOI: 10.5034/inquiryjrnl_47.01.62
|View full text |Cite
|
Sign up to set email alerts
|

Physician Quality and Health Care for the Poor and Uninsured

Abstract: Adverse health outcomes for uninsured patients have been attributed to their health status and to the quality of treatment received. A question about treatment that remains unexplored is whether physicians treating the uninsured are more likely to have characteristics indicative of lower quality than physicians treating insured patients. Using education, training, experience, and board certification to measure physician quality, we find that uninsured and Medicaid patients are treated by lower-quality physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…17 Regarding publicly insured adults, low payments are known to deter physicians from accepting Medicaid patients 19,34---36 and may also lead providers who accept Medicaid to hold these patients in lower regard. 17,37 Yet, a previous study using 2011 data indicated a relatively high Medicaid acceptance rate among Minnesota physicians (96%), 19 and low reimbursements may not be as much of an issue in Minnesota because the vast majority of nondisabled adults receiving Medicaid are enrolled through managed care programs. 38 The social stigma of public programs, especially Medicaid, 39,40 may contribute to a greater degree to the experience of insurance-based discrimination among Minnesota nonelderly publicly insured adults than do Medicaid reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Regarding publicly insured adults, low payments are known to deter physicians from accepting Medicaid patients 19,34---36 and may also lead providers who accept Medicaid to hold these patients in lower regard. 17,37 Yet, a previous study using 2011 data indicated a relatively high Medicaid acceptance rate among Minnesota physicians (96%), 19 and low reimbursements may not be as much of an issue in Minnesota because the vast majority of nondisabled adults receiving Medicaid are enrolled through managed care programs. 38 The social stigma of public programs, especially Medicaid, 39,40 may contribute to a greater degree to the experience of insurance-based discrimination among Minnesota nonelderly publicly insured adults than do Medicaid reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
“…12---16 Insurance-based discrimination is defined as the unfair treatment that patients receive from health care providers because of the type of insurance they have or because they do not have insurance. 12,15,16 For example, physicians may sort patients by their insurance status, 17 serving patients with public insurance differently than other patients. 18 Additional evidence lies in the fact that some physicians are not willing to accept Medicaid patients because of the low reimbursement rates.…”
mentioning
confidence: 99%
“…A study of hospitals in Florida has found some evidence that, compared to other patients in the same hospital, uninsured and Medicaid patients are treated by lower-quality physicians. 16 Third, Medicaid patients may be less likely to receive treatment with newer, more expensive forms of care than their privately insured counterparts, even in the same hospital. For example, Andrew Epstein and coauthors 17 found lower utilization rates of drug-eluting stents among Medicaid and uninsured patients than among privately insured patients in the same hospital.…”
mentioning
confidence: 99%
“…For example, some participants were able to receive medical care at a free clinic, but had no means of receiving comprehensive DSM education. Although the quality of care chasm has been previously documented (Steele & McBroom , Agency for Healthcare Research and Quality (AHRQ) , Gardner & Vishwasrao , Ricci‐Cabello et al . ), little attention has been paid to the actions individuals take to circumvent these limitations.…”
Section: Discussionmentioning
confidence: 99%